Effect of Acupuncture Therapy with Tomato Combination on Hemiparesis in Upper Extremity Dextra or Sinistra After Stroke at Griya Acupuncture Indy - Putri, Intan Tania Inanda; Haryanto, Joko Tri; Sholihah, , Imrok Atus (Indonesian Journal of Acupuncture, 2024)
The number of non-communicable diseases (NCDs) is getting higher every year, one of which is stroke. Stroke is a disorder characterized by rupture or blockage of cerebral blood vessels which can cause weakness and even paralysis of one side of the body. One of the treatments that can be done is acupuncture therapy which plays a role in repairing cell damage that occurs. In addition to therapeutic treatment, incoming food intake is no less important, tomatoes are one of the horticultural plants that have many benefits for post-stroke repair. This research is to determine the effect of acupuncture therapy with a combination of tomatoes on hemiparesis in the upper extremity dextra or sinistra after stroke at Griya Acupunture Indy. Using Quasi Experimental with two groups pretest-posttest design with Purposive Sampling sampling technique, the sample size was 30 research subjects. Divided into control groups and experimental groups with each group totaling 15 research subjects. MMT scale measurements were taken before and after performing 6 times of therapy. The points used include LI4 Hegu, PC6 Neiguan, LI11 Quci, and LI14 Binao. The result is p= 0.008, which means The results of this study indicate that acupuncture at LI4 (Hegu), PC6 (Neiguan), LI11 (Quchi), and LI14 (Binao), combined with tomato supplementation, is more effective in improving upper extremity muscle strength after stroke compared to acupuncture therapy only.